2010
DOI: 10.1002/bdra.20728
|View full text |Cite
|
Sign up to set email alerts
|

Ljungan virus: A commentary on its association with fetal and infant morbidity and mortality in animals and humans

Abstract: Epidemiologic and experimental data support the notion that Ljungan virus (LV), endemic in some rodent populations in Sweden, Denmark, and the United States, can cause morbidity and mortality in animals and humans. LV infection can cause type I diabetes mellitus, myocarditis, and encephalitis in bank voles and experimental mice, and lemmings. Mouse dams infected with LV experience high rates of stillbirth that may persist across generations, and their fetuses may develop cranial, brain, and limb malformations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
7
0
2
Order By: Relevance
“…However, in humans PUUV and TBEV infection may cause severe illness (Table 1). If LV infections cause disease in humans and/or in bank voles is controversial and remains to be clearly shown [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, in humans PUUV and TBEV infection may cause severe illness (Table 1). If LV infections cause disease in humans and/or in bank voles is controversial and remains to be clearly shown [6].…”
Section: Introductionmentioning
confidence: 99%
“…The pancreas from an asymptomatic bank vole, however, stained negative for LV and showed no such clusters [59]. These two studies have until now been the only to demonstrate an association between LV and diabetes in bank voles, and it has often later been stated, or taken for granted, that “LV causes diabetes in voles” [79][84]. However, since it is not possible to determine with accuracy whether a vole is infected with the LV, it follows that its possible role as an etiological agent responsible for diabetes in bank voles remains to be proven [60].…”
Section: Discussionmentioning
confidence: 94%
“…Taken together, these preliminary correlations imply that LV may play an important role in SIDS. However, Krous and Langlois () also reported that the evidence for LV being prominent in SIDS cases is not convincing.…”
Section: Sudden Infant Death Syndrome (Sids)mentioning
confidence: 99%
“…It has been reported that LV infection can result in type 1 diabetes mellitus, encephalitis and myocarditis (Blixt et al, ). Recently, a series of studies have found that LV is associated with severe diseases during pregnancy, such as malformation and fetal death during late pregnancy (Krous et al, ). This review focuses on stillbirth and fetal malformation.…”
Section: Ljungan Virusmentioning
confidence: 99%